Pengaruh Audit Manajemen Sumber Daya Manusia terhadap Kinerja Karyawan (Studi Kasus pada PT. Gramedia Asri Media Bandar Lampung) - Herry Goenawan Soedarsa; Chairul Anwar; . Shanti (Jurnal Akuntansi dan Keuangan, 2014)
PT. Gramedia Asri Media Bandar Lampung is a general bookstore that is engaged in the retail and distribution of books, school and office tools as well as multimedia products. The company as a business person should be able to deal with the changes and developments that exist both in the field of technology and social. Based on the description in the background, this research aims to determine the influence of Human Resource Management Audit against the Employee Performance at Gramedia Asri Media Bandar Lampung. The variables that examined in this research are Human Resource Management Audit (X) as Independent Variables and Performance (Y) as the Dependent Variable. The population of this research is the parts that related to the audit of human resource management and employee performance. Sampling in this research is based on saturation sampling technique. In this research the number of the samples which are used is 43 respondents.The data which is used in this research is primary data obtained from the questionnaires and interviews. To analyze the influence of Human Resource Management Audit (X) Toward Performance (Y), writer uses descriptive qualitative and quantitative methods, correlation coefficient, simple linear regression analysis, analysis of the coefficient of determination, and a t test. Based on statistical analysis obtained the following results: t test results are showed that the Human Resource Audit impact employee performance. This is indicated by tcount 5.743 while ttable of 1.68, based on the calculation that tcount> ttable then Ho is rejected or in the other words Ha is accepted. Based on these findings it can be concluded that the hypothesis which states "Human Resource Management Audit influence on Employee Performance" is acceptable.